Clinical analysis of surgical treatment for head and neck lymphatic malformations in children: a series of 128 cases. (3rd August 2019) - Wang, Shengcai; Du, Jiangnan; Liu, Yuanhu; Zhang, Jie; Ge, Wentong; Zhang, Yamei; Guo, Yongli; Li, Yanzhen; Zhang, Xuexi; Li, Xiaodan; Yu, Yongbo; Jin, Yaqiong; et al.
Abstract: Background: Lymphatic malformations (LMs) are caused due to abnormal lymphatic development, and mainly occur in neonates or young children. At present, the role of surgery in the treatment of head and neck LMs is still controversial, focusing mainly on surgical efficacy and indications. Objective: This study aimed to explore the effect and influential factors of surgical treatment in children with head and neck LMs, hoping to provide a basis for rational selection of surgical indications. Methods: This retrospective study enrolled 128 children with head and neck LMs and underwent surgical treatment in Beijing Children's Hospital from May 2007 to June 2016. They were classified into three morphological groups: macrocystic, microcystic, and mixed. Based on de Serres staging, they were divided into five groups: stage I to V. The local lesion control rate, complication rate, and recurrence rate were summarized and analyzed. Results: The rate of completely controlled and almost completely controlled in cases with head and neck LMs was 71.1%. The postoperative complication rate was 13.3%, and the postoperative recurrence rate was 11.9%. Statistically significant difference was found for local lesion control and postoperative recurrence rates between different morphological and clinical staging groups. Furthermore, the complication rate showed a significant difference between different morphological groups, but not between clinical staging groups. Conclusions: Surgical resection in children with macrocystic, low-stage, or neck-limited LMs demonstrated better therapeutic effect, with fewer complications. However, the effect remained poor and had more complications for microcystic, diffused and high-stage patients. High stage and incomplete resection are considered as the main factors for postoperative recurrence. Current staging system for LMs has important predictive value in the prognosis of head and neck LMs. For LMs in posterior pharyngeal space, plasma ablation has certain advantages.